Evolution and future perspectives of scientific journals in Peruvian public universities - Reategui Inga, Manuel (2023)
In Peru, scientific journals are in constant growth, as they seek to make visible the scientific work of licensed public universities. In this sense, the objective of this research was to evaluate the historical evolution and future perspectives of scientific journals in Peru. The research was carried out by reviewing the official web pages of each institution, taking into account the official list of universities authorized by the Superintendencia Nacional de Educación Superior Universitaria (SUNEDU). We reviewed journals that are included in the Sistema Regional de Información en Línea para Revistas Científicas de América Latina, el Caribe, España y Portugal (Latindex Catálogo 2.0), SciELO, Web of Science (WOS) and Scopus. Data analysis was performed by tabulation in Excel and Minitab 19. We found 205 scientific journals, 51 are indexed in at least one database (Latindex Catálogo 2.0, SciELO, WOS, or Scopus) and 154 in no database, which means that the editorial teams have an arduous task. Only four journals are indexed in Scopus (three belong to the Universidad Nacional Mayor de San Marcos and one to the Universidad Nacional de Trujillo). It is concluded that the evolution of the journals is a function of their Google Scholar H index. Likewise, support for public universities should be increased to promote the indexing of scientific journals to generate greater visibility of research at regional, national, and international levels of public universities in Peru. In this sense, future perspectives include incentive policies for researchers who publish in local journals.